Rancang Bangun Sistem Pemesanan Menu Pada Balen Coffee Kota Madiun Menggunakan Metode Extreme Programming - Susanti, Pratiwi; Putrian, Aurisha Lutvinda; Kurniawati, Inung Diah (Jurnal Sains dan Teknologi (JSIT), 2024)
Balen Coffee is a place that sells food and drinks with a café concept. The sales system currently used is coming directly to the place (dine-in) and using online applications such as grabfood and gofood. However, instead of having to order via GrabFood or GoFood, some customers choose to order via WhatsApp admin and then pick up their order when it is finished. This happens because they feel a little burdened by the cost of shipping orders because if they go through Grabfood or GoFood, sometimes it is not commensurate with the total purchase. This also has an impact on Balen Coffee's lack of online sales. The aim of this research is to overcome problems that arise, namely to provide a platform that is expected to alleviate customer problems in online ordering and can increase online sales at Balen Coffee. The development method used in developing this system is the Extreme Programming method. This system was built using the PHP programming language, the database uses MySQL using the Laravel framework. This research produces a menu ordering system at Balen Coffee, Madiun City, which provides the appearance and access rights for customers and admins. The menus on the website run normally and do not experience errors or bugs. In accessing the website, customers and admins do not experience problems so it is easy to use.